Síntese e propriedades fotocatalíticas de heteroestruturas TiO2/SnO2 - Mendonça, Vagner Romito de (2014)
Heterostructures, systems containing two dissimilar semiconductors in direct contact, has been applied in heterogeneous photocatalysis due to their electronic properties. This work aimed at studying heterostructures containing metallic oxides. Due to their suitable features, both anatase TiO2 and rutile SnO2 were chosen to compose a model-system. In the first part, this work dealt with the synthesis of TiO2/SnO2 heterostructures by using two different routes: the sol gel hydrolytic (Hid) and the polymeric precursor method (Prec). The heterostructures photocatalytic properties were evaluated by the photodegradation of rhodamine B dye (RhB) under UV radiation. The results showed that heterostructures were more active than pristine TiO2, the same used to make heterostructures. That finding was related to charge migration between oxides, a heterostructure feature, as showed by photoluminescence spectroscopy analysis. The homogeneity in the phase formation (i.e., SnO2 dispersion over TiO2) was influenced by the synthesis method, as showed by X ray diffraction, Raman spectroscopy and scanning electron microscopy with X ray microanalysis. The main RhB degradation mechanism was correlated with the process of OH radical generation, which in turn was related to the concentration and nature of the surface hydroxyl groups on the photocatalyst surface, as determined by infrared spectroscopy analysis. Accordingly, the polymeric precursor method was shown to be more adequate for dispersing higher amounts of SnO2 in comparison with the hydrolytic sol gel method. In the second part, due to the difficulty of a controlling morphology in a one-pot crystallization of two components, and to isolate the effect of charge migration between oxides, it was studied the possibility of obtaining heterostructures from pre formed nanoparticles by an aggregation and coalescence process induced by hydrothermal annealing. Morphologically xiv different oxides were separately synthesized and hydrothermally treated in different conditions. A kinetic model based on a diffusion controlled process was applied in the analysis of results. The ability of generating OH radicals under UV radiation was used to verify the charge migration. The results demonstrated the possibility of obtaining heterostructures by an aggregation followed by a coalescence process. It was also showed the charge migration between oxides, despite the interface being a point of charge recombination. The heterostructure formation was confirmed by comparing the heterostructure capability to generate OH radicals with anatase TiO2, the active phase, when treated in the same hydrothermal conditions.